Development based Extension Systems in India - C.R. Desai; P.L. Manohari (Journal of Agricultural Extension Management, 2025)
Management of agricultural extension has special relevance to meet the needs of the farmers. Speedy transfer of technological innovations to the farm level, necessitates emphasis on building synergy among the delivery systems. The extension activities in the country are carried out through Line Departments based on various sectors. To take advantage of the opportunities offered by the changing scenario it is necessary to understand the present working modalities of Line Departments with farmers. This paper attempts to study the present status of line departments in order to understand the organizational aspects, extension activities and services undertaken, infrastructure availability apart from departmental linkages with other institutions, aspects related to training, capacity building, income generation and suggest suitable measures for improving the performance of the system. The study revealed different aspects that need to be addressed to make the systems professionally competent, to play their roles effectively. These include reducing levels of hierarchy, filling up vacant staff positions, offloading some of the services on a public private partnership mode, promoting alternate service providers and allocating sufficient funds for capacity building